Corporate Financial Distress Risk: Influence of Business Strategy and Environmental Responsibility - Raihan Irfan Abdul Majid; Banu Witono (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study examines the impact of Cost Leadership, Differentiation, Environmental Performance, and Environmental Costs on Financial Distress in Energy and Basic Materials sectors listed on Indonesia Stock Exchange during 2021-2024. These sectors face unique challenges combining Economic Volatility with Substantial Environmental Responsibilities.Methodology: By using Purposive Sampling, 172 firm-year observations from 43 companies were analyzed through Multiple Linear Regression with the Grover Model, which demonstrates superior accuracy compared to traditional Financial Distress prediction models.Results: Results reveal that Cost Leadership (β=0.584, p<0.001) and Differentiation (β=3.748, p<0.001) significantly increase G-Score, which reduce Financial Distress risk, with Differentiation exhibiting dominant influence. Conversely, Environmental Performance (β=0.008, p=0.849) and Environmental Costs (β=-0.088, p=0.834) demonstrate statistically insignificant effects on short-term financial health. The model collectively explains 60.8% of Financial Distress variance (Adjusted R²=0.608).Applications/Originality/Value: This research provides original contribution by integrating Business Strategy and Environmental Responsibility variables, addressing critical gaps in existing literature that predominantly examines these factors separately in Indonesian emerging market context.